Visualization of UV and ECD spectra of E&Z isomers of N-(4′-Hydroxy-cinnamoyl)− 5- hydroxyanthranilic acid. (December 2022) - Sumayya, P.C.; Jalala, V.K.; Shameera Ahammed, T.K.; Muraleedharan, K.
Abstract: Avenanthramides are secondary metabolites most prominently found in oat (Avena sativa.L). These are amides of cinnamoyl-anthranilic acids derivatives. Due to their fascinating biological potential, these compounds have attracted the curiosity of chemists. Herein, the theoretical background of the electronic transition in UV-Vis and ECD spectra of the (E&Z) isomers of N-(4′-Hydroxy-cinnamoyl)− 5- hydroxyanthranilic acid was studied. The physical mechanism of the electron transfer process during light excitation is more intuitively described with two-dimensional and three-dimensional visualization methods. The characteristics of the UV-Vis spectrum were extended to the electron-hole conceptualization and the charge transfer process was described with charge difference density (CDD) and transition density matrix (TDM). The interaction mechanism between light and molecule in ECD is quantitatively revealed by the transition electric dipole moment, transition magnetic dipole moment, and their tensor product. A well-defined UV –Vis spectrum was obtained for the E isomer whereas the ECD spectrum for the Z isomer. Graphical Abstract: ga1 Highlights: UV-Vis and ECD spectra of AVA (E&Z) isomers were analyzed. 2-D visualization of TDM and the electric-magnetic interaction are carried out. A well-defined UV –Vis spectrum was obtained for E isomer. The high-intensity peaks in ECD was obtained for Z isomer.